The Visible: Element of the Social - Brighenti, Andrea Mubi (Frontiers in Sociology, 2017)
In the context of a social-theoretical take on the link between social life and visibility, this paper invites to shift the focus from visibility phenomena to the visible. A theory of visibility, it is submitted, must be constructed as a theory of the medium. In opposition to visibility as a set of formal relations, what the visible brings to the fore is the existence of a mid term, a connective tissue. Also, if a theory is a prelude to a science, then a theory is needed that makes possible to measure the visible in itself. The development of an ‘intrinsic’ theory of the visible, one capable of generating its own variables and constants, along with the conceptual space for their articulation, is retrieved through the joint contributions of surface theories (Simmel, Goffman, Portmann) and intensity theories (Deleuze, Thom). The piece presents a set of notions that could be of use to analyse the fibre of the visible and the trajectories occurring in the visible, in view of laying out a series of laws of the visible.